Envelhecimento e violência contra idosos - Dias, Isabel (2014)
This paper analyses the issue of population ageing and elderly abuse. An overview is presented of current sociological theory on ageing and an approach is developed to the difficulties found in defining the concept of elderly abuse. Abuse in the institutional setting will be particularly focussed upon.